Rainwater Harvesting-Based Conservation Model in Urban Flood Control: A Study at SMPN 24 Semarang - Rudi Salam; Ibnu Sodiq; Antari Ayuning Arsi; Nining Wahyuningsih; Mauren Anastasya (International Journal Labs, 2025)
When the rainy season arrives, one thing we often hear about is flooding in the lower regions. This can happen if land on higher plains loses part of its function due to several reasons, such as development that does not pay attention to green open space, and if rainwater is not captured and reused, causing water to flow directly to lower plains. Rainwater harvesting is a conservation and technological method used to collect and store rainwater from the roofs of buildings, ground surfaces, roads, or hills. One of the methods of harvesting rainwater that collects and stores it at ground level is infiltration wells and biopore infiltration holes. This research supports SDGs 6, Clean Water and Sanitation. The purpose of this research is to create a rainwater harvesting model expected to provide great benefits in flood prevention, with the location at SMPN 24 Semarang. The research method used is qualitative descriptive. The results of research in the field show that the method of harvesting rainwater through a roof system, namely capturing rainwater in gutters which is then stored in a water storage reservoir, is very suitable to be applied at SMPN 24 Semarang, considering that around the building there are gardens and taman that require watering, so the water collected can be used to water plants. Next is the biopore infiltration hole, which has the benefit of absorbing water and can also compost organic waste into compost, so that the plants in the garden and taman are more fertile.